2015
DOI: 10.1111/cogs.12316
|View full text |Cite
|
Sign up to set email alerts
|

A SPoARC in the Dark: Spatialization in Verbal Immediate Memory

Abstract: In 2011, van Dijck and Fias described a positional SNARC (Spatial-Numerical Association of Response Codes) effect: the SPoARC (Spatial-Positional Association of Response Codes). To-be-remembered items (e.g., numbers, words) presented centrally on a screen seemed to acquire a left-to-right spatial dimension. If confirmed, this spatialization could be crucial for immediate memory theories. However, given the intricate links between visual and spatial dimensions, this effect could be due to the visual presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
69
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 86 publications
(114 reference statements)
5
69
1
Order By: Relevance
“…Fruits or vegetables early in the sequence were responded to faster with the left-hand side and fruits or vegetables late in the sequence were responded to faster with the right-hand side. Recently, this ordinal position effect has also been replicated with auditory presentation of items (i.e., consonants) in WM (Guida et al, 2016). In this study, participants had to perform a slightly different task by pressing a "yes" or a "no" key to indicate whether the heard consonant was part of the memorized sequence or not.…”
mentioning
confidence: 85%
“…Fruits or vegetables early in the sequence were responded to faster with the left-hand side and fruits or vegetables late in the sequence were responded to faster with the right-hand side. Recently, this ordinal position effect has also been replicated with auditory presentation of items (i.e., consonants) in WM (Guida et al, 2016). In this study, participants had to perform a slightly different task by pressing a "yes" or a "no" key to indicate whether the heard consonant was part of the memorized sequence or not.…”
mentioning
confidence: 85%
“…In these models, order is coded through positional tags associated to each item. Even if no consensus has emerged concerning the actual nature of the positional tags, recent work on spatialization (e.g., Ginsburg et al, 2017;Guida, Carnet, et al, 2018;Guida, Leroux, et al, 2016;Rinaldi et al, 2015;van Dijck, Fias, & Andres, 2015) has showed that their nature could be spatial (see also Rinaldi, Merabet, Vecchi, & Cattaneo, 2018), like in the mental slotted line we are proposing.…”
Section: Slotted Schemas: the Spoarc Effectmentioning
confidence: 96%
“…The SPoARC effect has been observed (1) with short-term memory (STM) paradigms necessitating only storage (see second row of Fig. 1; e.g., Guida, Leroux, Lavielle-Guida, & Noël, 2016) and with WM paradigms necessitating storage and processing (e.g., ; (2) when order is relevant for the task completion (such as in the van , paradigm, in which participants have to recognize each sequence) or when order is irrelevant (i.e., without sequence recall or recognition; e.g., Guida, Leroux, et al, 2016); (3) with auditory (Guida, Leroux, et al, 2016) or visual input (e.g., ; (4) with verbal material (e.g., Ginsburg et al, 2014; or images (Ginsburg, Archambeau, van Dijck, Chetail, & Gevers, 2017); 5with open (Guida, Carnet, et al, 2018) or closed sets (e.g., ; (6) with an eye-tracking device (Rinaldi, Brugger, Bockisch, Bertolini, & Girelli, 2015); (7) with a line bisection task (Antoine, Ranzini, Gebuis, van Dijck, & Gevers, 2017); (8) when testing noncongenitally blind people, but not with the congenitally blind 1 (Bottini, Mattioni, & Collignon, 2016); and (9) when testing Arabic literates, for whom the effect is reversed (Guida, Megreya, et al, 2018). Umiltà, Bonato, and Rusconi (2018) have recently categorized SPoARC experiments as testing spatiotemporal associations because, in Westerners, the early items of a sequence are linked to left and the late to right.…”
Section: The Spoarc Effectmentioning
confidence: 98%
“…For instance, spatial-numerical associations could also stem from a general WM mechanism for binding sequential order with spatial templates (Abrahamse, van Dijck, & Fias, 2016;Guida, Leroux, Lavielle-Guida, & Noël, 2016), or from the principle of polarity correspondence in tasks with orthogonal stimulus dimensions (Proctor & Xiong, 2015). Particularly, we here focus on investigations into a domain-general cognitive mechanism for SNARC and aim to provide insights into the cross-validity of this mechanism for the generation of numerical SNARC and non-numerical SNARC-like effects in the ordinal weekday sequence.…”
mentioning
confidence: 99%